(untitled) (Biocenosis, 2023)
The Sustainable Development Goals (SDG) constitute a commitment by States to eradicate problems such as hunger, poverty or minimize damage to the environment, promoting actions for sustainable economic growth that is respectful of the environment. This requires education, technology, and the regulations that governments must impose on both their public institutions and private organizations. In this article we present the actions that the Costa Rican State has carried out to achieve the SDGs conditional on the agreements for the mitigation of climate change. Costa Rica has developed policies for the efficient use of energy and the promotion of education, among other actions aimed at fulfilling the SDGs. However, the COVID 19 pandemic generated negative effects, in terms of the implementation of public and private management and economic planning, which are aimed at achieving the resilience of human and natural systems. Likewise, complying with the SDGs is associated with the conservation of biodiversity and ecosystems, supported by proper management of water resources. Currently, the Costa Rican State is creating the financial and legal conditions to have the economic or financial resources required by the commitment to the SDGs.